Pengaruh Profitabilitas, Ukuran Perusahaan dan Kinerja Lingkungan Terhadap Pengungkapan Emisi Karbon Perusahaan (Studi Empiris Pada Perusahaan Pertambangan Sub Sektor - Melinda Magdarina; Ida Bagus Ketut Bayangkara (CV. Ulil Albab Corp, 2024)
The purpose of this study was to determine the effect of profitability, company size, and environmental performance on the disclosure of carbon emissions by coal mining industry companies on the Indonesia Stock Exchange (IDX) in 2020 to 2022. The research methodology used is a correlational quantitative approach using secondary data in the form of financial statements of 17 companies. Multiple linear regression was used for data analysis, with the independent variables profitability, company size, environmental performance and disclosure of Company carbon emissions information as dependent variables. The results showed that the profitability variable does not have a negative effect on the disclosure of carbon emissions, the company size variable does not have a positive effect on the disclosure of carbon emissions, and environmental performance variables have a positive effect on the disclosure of carbon emissions.